REDUCTION OF INTRA-ARTICULAR ADHESION BY TOPICAL APPLICATION OF DAIDZEIN FOLLOWING KNEE SURGERY IN RABBITS - Liu, Xiangchun; Jia, Heng; Xia, Hongsheng (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Intra-articular adhesion is the commonest complication that is faced by orthopedic surgeons after kneesurgery. Thus, the present investigation evaluates the effect of daidzein on intra-articular adhesion in rabbits.Material and methods: All the rabbits were separated in to four different groups each group carries ten rabbits. Cancellousbone was exposed in each rabbit by removing cortical bone from both side of the femoral condyle. Following daidzein (2.5,5 and 10 mg/ml) was topically applied for the duration of 10 min to the decorticated areas. Thereafter for the period of 4week surgical limb was fixed. Effect of daidzein on intra articular adhesion was estimated by visual score throughmacroscopic examination, histopathology study, hydroxyproline content, fibroblast and collage density.Results: Data obtained in the study suggest that topical application of daidzein (5 and 10 mg/ml) loose the collagen andsignificantly decreases the adhesion at the decorticated areas. Moreover there were significant reduction in the fibroblastdensity, hydroxyproline content and optical density of collagen tissue in daidzein (5 and 10 mg/ml) treated group thancontrol.Conclusion: Thus present study concludes that topical application of daidzein reduces intra-articular adhesion around theknee.